NUMERICAL STUDY OF CUTTING TEMPERATURE DURING DRILLING PROCESS OF THE C45 STEEL - Abdelkrim, Mourad; Brioua, Mourad; Belloufi, Abderrahim; Brabie, Gheorghe (International Journal of Modern Manufacturing Technologies, 2016)
Optimize the process and save time and cost are the main motivations for cutting tools modeling. Thus, the modeling of the drilling is a means for reducing the time and cost of designing new drill geometries. This work aims to propose thermal models in 2D and 3D in order to estimate the drill cutting temperature with and without metal coating during a drilling operation by using the digital simulation software Comsol Multiphysics. The results of thermal simulations for both types of drills with and without metal coating obtained underlines the importance of particular coatings TiN in the propagation of heat and the cutting temperature elevation.